Analisis Kreativitas Guru dalam Memanfaatkan Teknologi Digital di MIN 3 Jombang - Fania Wafiq Azizah; Evita Widiyati (eL Bidayah: Journal of Islamic Elementary Education, 2023)
Indonesia has entered an era of disruption, in this era the development of digital technology has become very rapid and has had an impact on the education sector. In connection with the development of digital technology, teachers must adapt to these changes, so that teachers are required to be creative. Teacher creativity can be carried out both in the learning process and outside of learning by utilizing digital technology. This study aims to determine teacher creativity in utilizing digital technology in learning and outside learning, as well as the inhibiting and supporting factors. The method in this study uses qualitative case study research. The results of this study are that the practice of utilizing technology-based learning has been implemented at State Islamic Elementary School 3Jombang by utilizing laptops and projectors to display learning media such as PPT, snakes and ladders, animated videos, interactive videos and puzzles. Outside of teacher learning utilizing digital technology for PPDB, Android-based Madrasa exams and school administration. Supporting factors in utilizing digital technology are adequate facilities, the ability of the teacher and the motivation of the Madrasah Principal. While the inhibiting factor is the lack of willingness, ability and knowledge of teachers in the use of digital technology. Students give positive responses when teachers use digital technology in learning, this makes students motivated in learning and improves student learning outcomes [Indonesia telah memasuki era disrupsi, dalam era ini perkembangan teknologi digital mejadi sangat pesat dan berdampak pada sektor pendidikan. Sehubungan dengan berkembangnya teknologi digital membuat guru harus beradaptasi terhadap perubahan tersebut, sehingga guru dituntut untuk kreatif. Kreativitas guru dapat dilakukan di dalam proses pembelajaran maupun di luar pem-belajaran dengan memanfaatkan teknologi digital. Penelitian ini bertujuan untuk mengetahui kreativitas guru dalam memanfaatkan teknologi digital di dalam pembelajaran dan di luar pembelajaran, serta faktor penghambat dan pendukungnya. Metode dalam penelitian ini menggunakan kualitatif dengan jenis penelitian studi kasus. Hasil dari penelitian ini yaitu praktik pemanfaatan pembelajaran berbasis teknologi sudah diterapkan di MIN 3 Jombang dengan memanfaatkan laptop dan proyektor untuk menampilkan media pembelajaran seperti PPT, ular tangga, video animasi, video interaktif dan puzzle. Di luar pembelajaran guru memanfaatkan teknologi digital untuk PPDB, ujian Madrasah berbasis android serta administrasi sekolah. Faktor pendukung dalam memanfaatkan teknologi digital yaitu fasilitas yang memadai, kemampuan dari guru serta motivasi dari Kepala Madrasah. Sedangkan faktor penghambatnya yaitu kurangnya kemauan, kemampuan dan pengetahuan dari guru dalam penggunaan teknologi digital. Siswa memberikan respon positif ketika guru menggunakan teknologi digital di dalam pembelajaran, hal ini membuat siswa termotivasi dalam belajar serta meningkatkan hasil belajar siswa]